Functional Fibrinolysis Assays Reveal Different Mechanisms underlying Plasminogen Dysfunction in Ligneous Conjunctivitis - Bourrienne, Marie-Charlotte; Loyau, Stéphane; Faille, Dorothée; de Raucourt, Emmanuelle; de Mazancourt, Philippe; Ho-Tin-Noé, Benoît; Gabison, Eric; Ajzenberg, Nadine (Thrombosis and Haemostasis, 2020)
Background Ligneous conjunctivitis (LC) is a rare disorder associated with plasminogen deficiency characterized by chronic fibrin deposits in the eyelids. All patients with plasminogen deficiency do not develop LC, whose underlying mechanisms remain unknown.Objective We investigated whether fibrinolytic activity was correlated with phenotype and/or genotype in patients suffering from LC and their relatives.Methods Plasminogen activity/antigen levels and PLG mutations were determined in 10 patients with LC, 17 of their asymptomatic relatives, and 10 healthy individuals used as a control group. Plasma fibrinolytic activity was evaluated using three different assays: (1) tissue-plasminogen activator (t-PA) front lysis, (2) cell-based urokinase-dependent euglobulin clot lysis (ECLT) at the surface of corneal cells, and (3) urokinase-dependent plasminogen activation.Results Plasminogen activity varied from <10 to 40% in patients, 36 to 105% in relatives, and >80% in control healthy individuals. Homozygous K19E mutation was associated with normal antigenic plasminogen levels. In front-lysis experiments, all patients had a lower fibrinolysis rate as compared with their relatives and to control individuals. The cell-based ECLT and plasminogen activation assay demonstrated that urokinase-mediated fibrinolysis was not impaired in patients with homozygous K19E mutation compared with the other mutants.Conclusion We confirm that plasminogen levels fail to predict LC occurrence. In these conditions, t-PA clot lysis front is useful to predict clinical outcome in plasminogen deficiency. Moreover, we provide evidence that occurrence of LC overlaps quantitative and qualitative plasminogen deficiencies. The homozygous K19E mutation is associated with isolated impaired t-PA-mediated fibrinolysis compared with other mutants.
Keywords: plasminogen; fibrinogen; fibrinolysis; plasmin; ligneous conjunctivitis